Training on Making Various Creations of Goods Using Used Paper - Merliyana, Merliyana; Saefurahman, Asep; Chandra, Rama; Burdah, Agustian; Hendrawati, Hendrawati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Training on making various creations of goods by utilizing waste paper is intended to foster interest in entrepreneurship. Entrepreneurial interest is preceded by knowledge and information which is then followed by participation in activities to gain experience, and finally, the desire to carry out these activities arises. The training was held in one day and was divided into an introduction to the concept of entrepreneurship and the practice of making various creations made from waste paper. The resulting products are not only of economic value but can also be used as everyday household appliances. This training is beneficial for the participants, because, in addition to increasing knowledge about entrepreneurship, it also adds skills, especially in making various creations of paper products. Utilizing social media and participating in MSME exhibitions which are relatively frequently carried out by the Central and Regional Governments, can be an alternative solution for product introduction and marketing.